Filosophical Views Of Al - Farabi (Eurasian Journal of History, Geography and Economics, 2024)
The article is dedicated to the philosophical views of Abu Nasr al-Farabi, one of the great thinkers of the Eastern Renaissance and a bright star of his era. This prominent philosopher, known in his time as "Muslim Al-Thani" (The Second Teacher) and the "Eastern Aristotle," left his ideas in his works.